2021
DOI: 10.1111/bjh.17932
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine therapy for advanced and indolent systemic mastocytosis: Mayo Clinic experience in 42 consecutive cases

Abstract: We describe our single institution experience with cladribine therapy in 42 patients with systemic mastocytosis (SM): 22 advanced (adv-SM; median age 65 years, 68% males) and 20 indolent/smouldering SM (ISM/SSM; median age 56 years, 45% males); subcategories included eight aggressive, 13 associated with another haematological neoplasm, one mast cell leukaemia, 17 ISM and three SSM. Overall/major response rates were 77%/45% for adv-SM and 70%/60% for ISM/SSM, and median (range) duration of response 10 (4-75) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…In historical cohorts of up to a maximum of 32 AdvSM patients [18,19,21], the ORR on cladribine according to (modified) Valent criteria [21,36] ranged between 50 and 100%. [20] Further interpretation on the impact of treatment with cladribine on progression-free (PFS), relapsefree (RFS), event-free (EFS), leukemia-free (LFS) and overall survival is limited because (i) most reports did not clearly differentiate between ISM and AdvSM, (ii) no report separated between 1L-and 2L-treatment and (iii) the definitions of PFS/RFS/EFS/LFS were not consistent between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In historical cohorts of up to a maximum of 32 AdvSM patients [18,19,21], the ORR on cladribine according to (modified) Valent criteria [21,36] ranged between 50 and 100%. [20] Further interpretation on the impact of treatment with cladribine on progression-free (PFS), relapsefree (RFS), event-free (EFS), leukemia-free (LFS) and overall survival is limited because (i) most reports did not clearly differentiate between ISM and AdvSM, (ii) no report separated between 1L-and 2L-treatment and (iii) the definitions of PFS/RFS/EFS/LFS were not consistent between studies.…”
Section: Discussionmentioning
confidence: 99%
“…inhibitor avapritinib [16,17], has extended the therapeutic options for patients with AdvSM, which were previously based on the off-label use of the purine analogue cladribine [18][19][20][21][22]. However, recent data on response rates and variably on leukemia-free (LFS), event-free-(EFS) and overall survival (OS) meanwhile favor the use of midostaurin and avapritinib [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another registry-based data analysis of patients with advanced SM, based on the MARS parameters and KIT D618V VAF, demonstrated the superiority of midostaurin versus cladribine regarding OS and leukemia-free survival [ 92 ]. Other studies showed that cytoreduction with cladribine successfully reduced the bone marrow mast cell burden and serum tryptase levels [ 93 , 94 , 95 , 96 , 97 , 98 ], particularly in patients with KIT D816V. A single institution study of 42 patients with advanced SM recently demonstrated that lack of KIT D816V mutation was an indication of cladribine resistance [ 93 ].…”
Section: Updates In Prognosis and Treatments For Systemic Mastocytosismentioning
confidence: 99%
“…Other studies showed that cytoreduction with cladribine successfully reduced the bone marrow mast cell burden and serum tryptase levels [ 93 , 94 , 95 , 96 , 97 , 98 ], particularly in patients with KIT D816V. A single institution study of 42 patients with advanced SM recently demonstrated that lack of KIT D816V mutation was an indication of cladribine resistance [ 93 ].…”
Section: Updates In Prognosis and Treatments For Systemic Mastocytosismentioning
confidence: 99%